The Second Heart Program-A multidisciplinary team supporting people who inject drugs with infective endocarditis: Protocol of a feasibility study. - Robin Lennox (Public Library of Science (PLoS), 2021)
Introduction Infective endocarditis (IE) is a severe and highly prevalent infection among people who inject drugs (PWID). While short-term (30-day) outcomes are similar between PWID and non-PWID, the long-term outcomes among PWID after IE are poor, with 1-year mortality rates in excess of 25%. Novel clinical interventions are needed to address the unique needs of PWID with IE, including increasing access to substance use treatment and addressing structural barriers and social determinants of health. Methods and analysis PWID with IE will be connected to a multidisciplinary team that will transition with them from hospital to the community. The six components of the Second Heart Team are: (1) peer support worker with lived experience, (2) systems navigator, (3) addiction medicine physician, (4) primary care physician, (5) infectious diseases specialist, (6) cardiovascular surgeon. A convergent mixed-methods study design will be used to test the feasibility of this intervention. We will concurrently collect quantitative and qualitative data and 'mix' at the interpretation stage of the study to answer our research questions. Ethics and dissemination This study has been approved by the Hamilton Integrated Research Ethics Board (Project No. 7012). Results will be presented at national and international conferences and submitted for publication in a scientific journal. Clinical trail registrarion Trial registration number: ISRCTN14968657 https://www.isrctn.com/ISRCTN14968657.